Species Sensitivity Distributions in Ecotoxicology - Posthuma, Leo (CRC Press, 2009)
In spite of the growing importance of Species Sensitivity Distribution models (SSDs) in ecological risk assessments, the conceptual basis, strengths, and weaknesses of using them have not been comprehensively reviewed. This book fills that need. Written by a panel of international experts, Species Sensitivity Distributions in Ecotoxicology reviews the current SSD methods from all angles, compiling for the first time the variety of contemporary applications of SSD-based methods.